Situating human resource management in the political economy: Multilevel theorising and opportunities for kaleidoscopic imagination. (6th November 2020) - Vincent, Steve; Bamber, Greg J.; Delbridge, Rick; Doellgast, Virginia; Grady, Jo; Grugulis, Irena
Abstract: This article introduces a special issue on Situating Human Resource Management (HRM) Practices in their Political and Economic Contexts . We develop a novel multilevel framework for exploring the political economy of HRM and use this to position the articles in this special issue. We argue that the study of HRM is often too narrowly constructed within a psychological, positivistic paradigm and at an organisation‐level, and that situating HRM in its political and economic context requires a more inclusive, interdisciplinary approach that includes the use of kaleidoscopic imagination and meta‐theoretical bricolage . By embracing a theoretically pluralist approach to studying HRM, researchers are better able to analyse how different levels of the political economy interact with specific HRM practices to impact value creation. We conclude by discussing the contribution of this article and the special issue, as well as highlighting avenues for future research.